PELATIHAN DESAIN APLIKASI CANVA DALAM MENINGKATKAN SOFTSKILL MAHASISWA STIE INDONESIA JAKARTA DENGAN MEDIA HANDPHONE - Haholongan, Rutinaias; Indriani, Agustina; Aeniyah, Aeniyah; Septiani, Shintia; Fuad, Zahwa Khalisha; Rumsia, Rika (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Increasing soft skills in students is crucial in facing the digital era. This journal examines the effectiveness of Canva application design training in improving the soft skills of students. This training aims to improve students' graphic design skills, creativity and visual communication skills. The method used is a direct tutorial, where students are guided to understand and operate Canva. Data is collected through overall research and documentation. As a result, students are expected to be able to apply these skills in society and have the potential to open a business, thereby increasing their creativity and independence in the digital era.